Business career management of company staff - Wang Liting (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of research is a process of managing the business career of staff. The subject of research is the theoretical and applied aspects of the process of planning and development of the business career of company staff. The purpose of the master's thesis is a scientific substantiation of the theoretical and methodological foundations and practical aspects regarding the improvement of the process of managing the business career of company staff. The obtained results are of significant practical importance, as the theoretical propositions, conclusions, and proposals developed through the research have been systematically transformed into practical methodological tools. These tools can be directly applied in enterprise operations to optimize and enhance the management system for personnel business careers. By implementing these developments, enterprises can improve the processes of career planning, talent development, and overall workforce management, ultimately contributing to increased organizational efficiency, employee satisfaction, and long-term strategic success.
Scientific advisor: Morozova N., PhD in economics, associate professor, department management, business and professional communications
Keywords: SOCIAL SCIENCES::Social sciences; management; сompany; business career; business career management system; career development management system